Embodied victims: an archaeology of the ‘ideal victim’ of restorative justice - Maglione, Giuseppe (Criminology & criminal justice, 2017)
This article seeks to provide a historical-critical framework to reconstruct and discuss how the crime victim is portrayed within theoretical literature, policy and legal documents on restorative justice, with an emphasis on England and Wales. It first centres on a description of the most deep-rooted and wide-ranging discourses on the victim’s characteristics within restorative justice. Once these features have been organized into an ‘ideal’ model, the article traces the conditions which fed into its development, that is, the cultural context within which this model has emerged. The overall goal is not to test the ‘ideal victim’ within restorative justice, but rather to explore how this methodological tool, within a historical and critical approach, might help to shed light on some taken-for-granted assumptions of restorative justice and their legal, policy and practical implications, thus contributing to the critical assessment of this acclaimed “new frontier” of contemporary penality.